2020
DOI: 10.3390/rs12172786
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Geosynchronous and Polar Orbiting Satellites: Sharing Best Practices

Abstract: Earth remote sensing optical satellite systems are often divided into two categories—geosynchronous and sun-synchronous. Geosynchronous systems essentially rotate with the Earth and continuously observe the same region of the Earth. Sun-synchronous systems are generally in a polar orbit and view differing regions of the Earth at the same local time. Although similar in instrument design, there are enough differences in these two types of missions that often the calibration of the instruments can be substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…According to Babu and Green et al [44,45], the uncertainty associated with AVIRIS measurements was around ~8.6% for all bands. According to Barsi and Helder et al [46,47], the uncertainty associated with the temporal and absolute temporal trend of L8 was within 2% for all bands. After obtaining the uncertainties associated with the input parameters of the ELM SR model, the ELM generates atmospheric coefficients (gain and bias) were calculated within their uncertainties using Monte-Carlo Simulation Method.…”
Section: Uncertainty Analysismentioning
confidence: 65%
“…According to Babu and Green et al [44,45], the uncertainty associated with AVIRIS measurements was around ~8.6% for all bands. According to Barsi and Helder et al [46,47], the uncertainty associated with the temporal and absolute temporal trend of L8 was within 2% for all bands. After obtaining the uncertainties associated with the input parameters of the ELM SR model, the ELM generates atmospheric coefficients (gain and bias) were calculated within their uncertainties using Monte-Carlo Simulation Method.…”
Section: Uncertainty Analysismentioning
confidence: 65%
“…In order to achieve better correction results, it was necessary to extend the application of the correction model to the entire plateau and achieve correction of summertime GIIRS temperatures over the entire plateau. Due to the orbit height of polar-orbiting satellites being lower than that of geostationary satellites, the observation accuracy of polar-orbiting satellites is often higher [34,35]. Research on the accuracy of IASI temperature profile products showed that IASI temperature products have good reliability and accuracy [36][37][38].…”
Section: Correction Model Based On the Iasi Level2 Temperature Productmentioning
confidence: 99%
“…Additionally, the uncertainty related to SBAF correction is computed based on Equation ( 27) below. Lastly, the temporal uncertainty of the orbital sensor (L8 OLI) SR is determined by utilizing the L8 OLI Level 1 temporal uncertainty [41].…”
Section: Uncertanties In Validation Of Landsat 8 With Respect To Arab...mentioning
confidence: 99%